The Use of Problem Based Learning In Developing Writing Skills of Grade VII Students of MTS Al-Khairaat Tondo - Sri Wulandari, Riska; Hastini, Hastini (Journal of General Education and Humanities, 2024)
This research is intended to prove that Problem-Based Learning can develop the writing skills of grade VII students of MTs Al-Khairaat Tondo. The study employs a quasi-experimental research design to assess the impact of PBL on students' abilities in writing procedure text. The researcher chose VII B and VII C Class as the sample for the study by using purposive sampling. The data were analyzed statistically to determine the significant difference in the student’s achievement before and after treatment. The results show the T-counted value of 5.95, surpassing the critical T-table value of 2.045. Consequently, the research hypothesis is accepted, signifying that implementing problem-based learning significantly contributes to developing writing skills among Grade VII students at MTS Al-Khairaat Tondo in constructing procedure text.